Developing Wearable Robot that Mimics Natural Walking Mechanism to Support Children with Cerebral Palsy in their Lower Limbs - Al-Abasi, Mariam Muhammad; AlKhwaji, Abdusalam Imhmed K. (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
A pioneering "Crank-Rocker" mechanism was developed in industrial biomechanics to simulate natural walking in a wearable robot. The project aims to assist children with lower limb motor impairments and reduce the robot's cost by minimizing the number of motors. An 8-year-old child model, weighing 16 kg and measuring 116 cm in height, suffering from lower limb motor impairment, was selected. The mechanism was designed using rigid elements inspired by the human leg's anatomy (bones and muscles) to simulate the muscular systems in wearable robots. The condition causes muscle atrophy, affecting bone movement and range of motion control. The mechanism consists of two main parts: the driving part, powered by a DC motor, which represents the Crank-Rocker mechanism, and the dependent part, representing the human leg. The mechanism was transformed into a multi-arm system, reducing the number of motors per foot to a single motor. A motor with a movable shaft structure was incorporated, connecting both feet with a single motor to ensure instantaneous synchronization of their movement. This also contributed to simplifying the control system and reducing the economic cost. The movement of the mechanism was simulated using SolidWorks, and a mathematical model for motion analysis was created using the closed-loop method. Additionally, Kinova software was used to analyze the movement and compare it with that of a healthy child. The results showed that the mechanism achieves a similar motion pattern to the natural walking of healthy children within GMFCS levels III and IV, enhancing the effectiveness of the mechanism in closely replicating a natural walking pattern. This project aims to assist children with lower limb motor impairments and reduce the robot's cost by minimizing the number of motors, thereby improving their quality of life.
Keywords: Biomechanics; Crank-Rocker mechanism; Wearable robot; Cerebral palsy; KINOVA